Analysis of Marketing Mix Strategies to Enhance Brand Awareness in Restaurants in Denpasar City - Samin; Gede Sri Darma (Jurnal Manajemen Bisnis, 2024)
In an era of fierce competition and ever-changing consumer trends, a deep understanding of purchase intent is essential for a company's survival and growth. This study aims to examine the impact of marketing mix strategies on brand awareness in restaurants in Denpasar. The research employs a quantitative descriptive approach, involving 150 respondents. The results indicate that the marketing mix—comprising product, place, price, promotion, and service quality—positively influences brand awareness, particularly when moderated by digital marketing. Furthermore, increased brand awareness significantly affects customers' purchase decisions and repurchase intentions. Based on these findings, it is recommended that restaurant businesses focus on the factors of the marketing mix to enhance brand awareness, thereby influencing customers' purchase decisions and encouraging repurchase behavior.